The effect of the production supports and the greening onto the sowing construction in Békés County - Rákóczi, Attila (JOURNAL OF LANDSCAPE ECOLOGY, 2018)
Békés County has good agricultural qualities: one of these important qualities is the high quality arable land. Almost the whole area of the county is used for arable farming. Apart from the high quality crops it is important that high production rates are typical at this area. Due to these factors set-aside was not common practice only were used where crop rotation and agrotechnics required it. The Common Agricultural Policy (CAP) called Agenda2000 already suggested the requirement of set-aside, however, it was not used by Hungarian farmers for years in practice. The latest reform generated by the CAP has brought many new requirements for farmers related to the payment of agricultural support. Among these are the spectrum of greening requirements. During our research we examined the land using data in the county from 2009 to 2016. We analyzed the statistics from the perspective of area-data and use of land. We determined that in the general crop rotation of the farms, the area of a few main crops was typically decreased and plant diversification in agricultural areas grew, the ratio of set-aside lands significantly increased to the „disadvantage” of cultivars. Support dependent on plant-based production only caused an increase in cultivated areas in a few cases. It is apparent that the county's cultivation structure has changed greatly in the past nine years in the interest of maximum access to agricultural support via the KAP (Common Agricultural Policy) reforms, however, in the case of certain emphasized crops, the desire to produce has not grown despite production-dependent support.
Keywords: common agricultural policy; direct payments; production supports; greening